INSIDE THE IRON DOME. - Raviv, Dan (Moment Magazine)
The article offers information on Iron Dome, a mobile all-weather air defense system developed by Rafael Advanced Defense Systems and Israel Aerospace Industries. It is mentioned that the system is designed to intercept and destroy short-range rockets and artillery shells fired. The article also offer information on testing, development, and funding of the project and how Israel hopes to increase the range of Iron Dome's interceptions.